Pengaruh Penggunaan Aplikasi Aurora 3D Presentation Terhadap Hasil Belajar Ilmu Pengetahuan Alam IPA Siswa Pptq Jami'ul Qurra'Bajeng Barat Kabupaten Gowa - Nurhalisa, St.; Nawir, Muhammad; Nurindah (Jurnal Riset Guru Indonesia, 2025)
Abstract. The Effect of Using Aurora 3D Presentation Learning Media on Science Learning Outcomes of Pptq Jami'ul Qurra' Bajeng Barat Students, Gowa Regency. Thesis for the Educational Technology Study Program, Faculty of Teacher Training and Education, Muhammadiyah University of Makassar. Advisor I Muhammad Nawir and Advisor II Nurindah.This study aims to determine the Effect of Using Aurora 3D Presentation Learning Media on Science Learning Outcomes of Pptq Jami'ul Qurra' Bajeng Barat Gowa Regency Students. The sample in this study was class VIII students of Pptq Jami'ul Qurra' Bajeng Barat for the 2021/2022 academic year, a total of 16 students. From the results of these data it can be concluded that through the Aurora 3D Presentation learning media in science learning class VIII students of Pptq Jami'ul Qurra' Bajeng Barat and gave a positive response to the learning media. Based on the results of research and data analysis regarding the comparison of statistical values ​​and comparison of learning outcomes categories, it has been proven that there is a positive effect of using Aurora 3D Presentation media on student learning outcomes in class VIII Pptq Jami'ul Qurra' Bajeng Barat, which can be seen from student learning outcomes through descriptive statistical analysis before using the Aurora 3D Presentation media, the average student score is still in the low interval category and after using the Aurora 3D Presentation media, the average student score is in the high interval category. It is known that the average value of the Pretest results is 28.43 and the average value of the Posttest results is 72.5 where the Posttest value is greater than the Pretest value. Furthermore, based on the results of inferential statistical analysis using the t test formula, it is known that the tcount obtained is 15.69 with a frequency df = 16-1 = 15, at a significant level of 0.05 or 5%, the ttable is 1.753. So tcount > ttable or H0 is rejected, H1 is accepted.Keywords: Media Aurora 3D Presentation, Learning Outcomes